Antimicrobial peptides and proteins: Interaction with the skin microbiota. Issue 10 (30th July 2021) - Rademacher, Franziska; Gläser, Regine; Harder, Jürgen
Abstract: The cutaneous microbiota comprises all living skin microorganisms. There is increasing evidence that the microbiota plays a crucial role in skin homeostasis. Accordingly, a dysbiosis of the microbiota may trigger cutaneous inflammation. The need for a balanced microbiota requires specific regulatory mechanisms that control and shape the microbiota. In this review, we highlight the present knowledge suggesting that antimicrobial peptides (AMPs) may exert a substantial influence on the microbiota by controlling their growth. This is supported by own data showing the differential influence of principal skin‐derived AMPs on commensal staphylococci. Vice versa, we also illuminate how the cutaneous microbiota interacts with skin‐derived AMPs by modulating AMP expression and how microbiota members protect themselves from the antimicrobial activity of AMPs. Taken together, the current picture suggests that a fine‐tuned and well‐balanced AMP‐microbiota interplay on the skin surface may be crucial for skin health.